2016
DOI: 10.1111/nph.14191
|View full text |Cite
|
Sign up to set email alerts
|

Defense traits in the long‐lived Great Basin bristlecone pine and resistance to the native herbivore mountain pine beetle

Abstract: Summary Mountain pine beetle (MPB, Dendroctonus ponderosae) is a significant mortality agent of Pinus, and climate‐driven range expansion is occurring. Pinus defenses in recently invaded areas, including high elevations, are predicted to be lower than in areas with longer term MPB presence. MPB was recently observed in high‐elevation forests of the Great Basin (GB) region, North America. Defense and susceptibility in two long‐lived species, GB bristlecone pine (Pinus longaeva) and foxtail pine (P. balfouriana)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 91 publications
6
52
0
Order By: Relevance
“…longaeva (0.015 mm 2 ; ~2 ducts per year), and P . balfouriana (0.030 mm 2 ; ~5 ducts per year; Bentz et al, ; Ferrenberg et al, ). However, the range of sizes and production of resin ducts in both species at our sites overlapped with these other populations, indicating substantial between‐site variability due to potential environmental, genetic, or interacting factors (Ferrenberg et al, ; Hood & Sala, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…longaeva (0.015 mm 2 ; ~2 ducts per year), and P . balfouriana (0.030 mm 2 ; ~5 ducts per year; Bentz et al, ; Ferrenberg et al, ). However, the range of sizes and production of resin ducts in both species at our sites overlapped with these other populations, indicating substantial between‐site variability due to potential environmental, genetic, or interacting factors (Ferrenberg et al, ; Hood & Sala, ).…”
Section: Discussionmentioning
confidence: 99%
“…These processes have linkages, in that resin cells extend throughout the plant to produce and deliver chemicals in attacked tissues (Björkman, Larsson, & Gref, ; Zas et al, ). Although some studies examined both anatomical and chemical components of tree defence (Bentz, Hood, Hansen, Vandygriff, & Mock, ), or within‐tree correlations within seedlings (Moreira, Zas, Solla, & Sampedro, ), to our knowledge, none have tested their relatedness within the same mature trees or compared relationships between species of different exposure histories.…”
Section: Introductionmentioning
confidence: 99%
“…However, although a beetle species is capable of moving into new landscapes, this does not mean that the new tree species it encounters will be a susceptible host (Bentz et al . ). Similarly, regionally synchronous outbreaks are not necessarily a given, and only a few studies have explored how past climate dynamics influenced outbreak synchrony and intensity at any spatial scale (Jarvis and Kulakowski ).…”
Section: Synthesismentioning
confidence: 97%
“…These differences indicate that the relationship between resin duct defense and climate likely varies depending on the species and the climatic regions examined. Recent research has observed substantial variation in defense characteristics in pines across sites of differing climate [65] and along elevational gradients [66], but more direct examination with climate across these scales is needed.…”
Section: Defense Relationships With Climate and Competitionmentioning
confidence: 99%